2016
DOI: 10.5334/jbr-btr.1159
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Coated Balloon Angioplasty of Venous Stenoses in Native Dialysis Fistulas: Primary and Secondary Patencies at 6 and 12 Months

Abstract: Purpose:When dialysis access stenoses are dilated by noncoated balloons, respective primary and secondary patencies hardly reach 50 per cent and 85 per cent at one year. This study determines the primary and secondary patency rates at 6 and 12 months for venous stenoses treated by paclitaxel-coated balloon (PCB) angioplasty in native hemodialysis accesses.Materials and Methods:From 2012 to 2014, 70 venous stenoses in 41 patients benefited from PCB angioplasties. The patients’ mean age was 62.5 ± 13.8 years’ st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Moreover, a recent randomized controlled clinical trial has shown good outcomes of PCBA for stenosis in dialysis access ( 10 22 ). Other recent non-randomized studies have also reported good outcomes of PCBA for the treatment of stenosis of native dialysis fistula and in-stent stenosis of dialysis fistula ( 23 24 ).…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, a recent randomized controlled clinical trial has shown good outcomes of PCBA for stenosis in dialysis access ( 10 22 ). Other recent non-randomized studies have also reported good outcomes of PCBA for the treatment of stenosis of native dialysis fistula and in-stent stenosis of dialysis fistula ( 23 24 ).…”
Section: Discussionmentioning
confidence: 84%
“…This randomized controlled trial (RCT) aimed to investigate the potential added value of DCBs in patients with dysfunctional autogenous AVFs, focusing on a specific access type to lessen heterogeneity. This RCT has two main strengths: it is the first randomized comparative study to evaluate the efficacy of DBA exclusively in dysfunctional RCAVFs as opposed to other types of dialysis access, and it has a relatively long follow-up period compared to previously published studies ( 9 10 12 16 17 18 19 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, multiple observational and randomized controlled studies have evaluated the use of DCBs for prolonging patency, but caution should be taken when interpreting the results due to clinical heterogeneity resulting from the non-uniform level of intervention ( 8 9 11 12 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ). In a retrospective study in 2014, Patanè et al ( 9 ) presented a case series of 26 patients who had juxta-anastomotic radiocephalic stenosis treated using DBA.…”
Section: Discussionmentioning
confidence: 99%
“…Although a significant difference occurred in favor of PCB at 6 months, there was no significant difference between treatments at 1 year (at 6 months: PCB 70% vs. CBA 0%; p<0.01; at 1 year: 20% vs. 0%; p>0.05) (15). A recent prospective single-arm study came from Verbeeck et al (16) using IN.PACT PCB (Medtronic, Brescia Italy). Primary patency rates were 81.4% ± 4.6% and 60% ± 5.9% at 6 and 12 months, respectively (16).…”
Section: Paclitaxel-coated Balloons In Vascular Accessmentioning
confidence: 99%
“…A recent prospective single-arm study came from Verbeeck et al (16) using IN.PACT PCB (Medtronic, Brescia Italy). Primary patency rates were 81.4% ± 4.6% and 60% ± 5.9% at 6 and 12 months, respectively (16). Finally, another three retrospective studies are available in the literature each one with a specific characteristic.…”
Section: Paclitaxel-coated Balloons In Vascular Accessmentioning
confidence: 99%